Pengelolaan Hipertensi Lansia Melalui Penguatan Posyandu Lansia dan Pemberdayaan Masyarakat di Desa Kutampi, Nusa Penida - I Putu Suiraoka; I Made Bulda Mahayana; Listina Ade Widya Ningtyas; Ida Bagus Made Putra Mahendra (Poltekita: Jurnal Pengabdian Masyarakat, 2026)
Based on observations among the elderly group, it was found that out of 112 respondents, nearly half (45.5%) suffered from hypertension. However, only 6.3% of the elderly regularly attended Posyandu Lansia (Elderly Integrated Health Post) activities. Currently, services provided at the Posyandu include exercise sessions, health education, and medical check-ups. The objectives of this community service program were to: (1) empower Posyandu cadres, (2) provide education for the elderly regarding a healthy environment, balanced diet, oral health maintenance, and self-acupressure techniques, and (3) offer blood pressure monitoring and acupressure services at the Posyandu Lansia in Kutampi Village. The methods applied in this program included community empowerment, health education, and direct health services. The target participants were Posyandu cadres and elderly residents of Kutampi Village, with activities conducted from June to November 2025. Program success was measured based on attendance and improvement in participants’ knowledge. The cadre empowerment program for elderly hypertension management involved 27 cadres who participated in the training sessions. Strengthening the Posyandu Lansia was achieved through educational activities on hypertension, healthy environments, and appropriate dietary choices for hypertension, along with blood pressure measurement and acupressure services. The program received strong support from the Village Head of Kutampi and the Head of Nusa Penida I Public Health Center. Post-education evaluations showed an improvement in participants’ knowledge.